Strategy of Agro Potential Management as an Effort in Achieveing Agroecotourism in Ciburial Village - Dedeh Ekawati; Yusuf Arifin (TRIKONOMIKA, 2016)
This study aims to identify and analyze the external and internal environment, opportunities, threats, strengths, and weaknesses of the management potential of agro, agro potential strategic management priorities, along with appropriate management programs that can be implemented by the manager. The results are expected to contribute in the development of tourism management, especially management. The study was conducted in Ciburial Village, Cimenyan District of Bandung Regency. The research method used was survey with descriptive and qualitative approach. Method analysis used were IE (Internal-External) analysis, SWOT (Strengths, Weaknesses, Opportunities, Threats) Analysis, and AHP (Analytical Hierarchy Process). The results showed that the management of agro potential in the growth stage requires the manager of the Ciburial Village to cooperate with the various stakeholders involved in the management of agro potential mainly through increased community participation.